Pain is a leading component of quality of life in patients with osteoporotic femoral fractures and approaches to its treatment - Yu. V. Averkieva; T. A. Raskina; M. V. Letaeva (Современная ревматология)
Chronic pain (CP) is an independent clinical syndrome that determines to the greatest extent dysfunction and lower social standing in a patient.Objective: to assess quality of life (QL) in old patients with osteoporotic femoral fractures.Subjects and methods. QL was assessed in 219 patients from an old age group (mean age 75.4±9.27 years) with osteoporotic proximal femoral fractures (a study group). A control group consisted of 200 examinees (mean age 71.5±10.39 years) without a history of fractures. QL was assessed using the SF-36 questionnaire. The results were presented in scores; moreover, a higher score denoted a better QL.Results. In the patients with femoral fractures, the QL indicators were decreased to a greater degree and in the majority of parameters than in the control group. The least values were obtained in the following scales: physical functioning (41.94±31.16 scores) and role functioning caused by physical condition (42.34±27.2 scores). The patients with femoral fractures had significant limitations in all types of physical activity, at the same time they experienced severe pain and felt tired and vitality loss.Chronic pain syndrome is shown to have impact on worse QL. The issues of combination therapy are discussed.